Hypersonics : Next Big Thing or Next Big Fad? - Bitzinger, Richard A. (2020)
Hypersonic weapons are seen by many as the “next big thing,” and, as such, great power militaries appear to be a hypersonics arms race. There are, however, many technical challenges to deploying an effective hypersonic weapon, and, even then, its impact on military balances may be less than projected.